(untitled) (Research, Society and Development, 2021)
The supervised internship is the period in which the academic begins his professional experience and puts into practice the knowledge acquired during theoretical and practical classes. Institutions with school clinics provide their students with a realistic experience of their future profession, promoting an internship field and providing free services to the entire community. Objectives: To present the sociodemographic, clinical and satisfaction profile of the participants of the Clinic School of Physiotherapy (CEF) of the Educational Institute Santa Catarina/Faculdade Guaraí (IESC/FAG), which offers free care to the population of the municipality of Guaraí-TO and region, through a partnership with the Municipal Health Department. Methodology: This is a descriptive and quantitative and qualitative cross-sectional study, through the application of a questionnaire with 18 questions that addressed sociodemographic, clinical and satisfaction issues with 49 participants of the CEF. Results: There was a predominance of female participants with 53.07%, complete high school is the level of education of 30.62% of participants and income below 2 minimum wages is the reality of 79.59%. The most comprehensive functional changes in FEC treatments are balance and gait deficits (10) and the Neurofunctional area has 32.65% of demand. The perception of great satisfaction with the interns’ care reached 76% among the participants. Conclusion: This result reaffirms the social commitment that the CEF of IESC/FAG has to the community of the municipality of Guaraí and region, since for most of its participants, this is the only guarantee of access to physical therapy assistance.